Chinese EFL teachers’ desire to attend professional development programs: Exploring the role of job satisfaction and organizational commitment - QI, JIAMING; DERAKHSHAN, ALI (Porta Linguarum An International Journal of Foreign Language Teaching and Learning, 2023)
The influence of teachers’ inner forces and factors in professional development (PD) has been highlighted in the past decades. However, little is written about the interplay of English as a foreign language (EFL) teachers’ desires to attend PD programs and their perceived job satisfaction and organizational commitment. To fill this gap, this study used three questionnaires to inspect the relationships among these three constructs. It also aimed to showcase whether Chinese EFL teachers’ desire to attend PD programs is predicted by their job satisfaction and organizational commitment. Adopting a random sampling technique, a sample of 357 EFL teachers was recruited from different colleges and universities in China. The results of Structural Equation Modeling (SEM) and correlation analysis revealed a positive and strong correlation between teachers’ job satisfaction, organizational commitment, and their desire to attend PD programs. Moreover, it was found that both job satisfaction and organizational commitment could collectively predict around 73% of changes in teachers’ desire to attend PD programs. The results are discussed and implications for the theory and practice of second/foreign language (L2) education in light of psycho-affective factors are enlisted. FUNDING INFORMATION. This work was supported by “Jiangsu Provincial Social Science Fund of China” (Grant No.: 22ZWD001).